Post Oeprative Sore Throat (POST), Comparison Between Nebulization with Ketamine and Placebo - Rifah Zia, Shahid Iqbal, Mohammad Baqir Ali Khan, Muhammad Muazzam Butt, Tahir Nazeer, Muhammad Zahid Hanif (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the frequency of post-operative sore throat with nebulized ketamine versus nebulized placebo pre- operatively in patients undergoing elective surgery under general anaesthesia. Study design; Randomized Controlled trial. Setting; Department of Anesthesia, Hameed Latif Hospital, Lahore. Duration of study; 08-05-2018 to 08-11-2018. Methodology: In this study, the cases of either gender and age range of 18 to 40 years undergoing elective surgery under GA requiring endotracheal tube were selected. The cases in Group A were nebulized with Ketamine (50 mg) mixed with normal saline while those in group B with normal saline only for 15 minutes. They were assessed at 4 hours on the basis of verbal response scale (VRS) after extubation regarding cough and irritation in the throat and score of 4 or more on VRS was labelled as POST. Results: In this study out of 40 cases in each group males were 23 (57.5%) vs 26 (65%) and mean age was 34.21±4.21 vs 32.57±4.67 years in group A and B respectively. Post operative sore throat was seen in 8 (17.5%) in group A and 18 (45%) in group B with p= 0.01. This difference was significant in terms of female gender where this was seen more in females in group B 64.28% vs 11.76% (p= 0.001). This difference was also significant in cases with duration of surgery more than 60 minutes where it was seen in 14.28% vs 44.34% in group A and B respectively (p= 0.01) Conclusion; Ketamine nebulization is significantly better for POST than placebo and this difference is also significantly high in terms of female gender and duration of surgery > 60 minutes. Keywords;